Antioxidants in Animal Feed - Jie Wang; Wei Si; Zhenyu Du; Junmin Zhang; Min Xue (MDPI AG, 2022)
Production animals are often exposed to several oxidative stress conditions, including, but not limited to, heavy metals, alternative protein sources, environmental stress, disease, high densities, as well as handling, which may suppress growth performance, animal health and production, subsequently impacting economic feasibility [...]